Metabolic Bone Disease in the Bariatric Surgery Patient - Susan E. Williams (Journal of Obesity)
Bariatric surgery has proven to be a life-saving measure for some, but for others it has precipitated a plethora of metabolic complications ranging from mild to life-threatening, sometimes to the point of requiring surgical revision. Obesity was previously thought to be bone protective, but this is indeed not the case. Morbidly obese individuals are at risk for metabolic bone disease (MBD) due to chronic vitamin D deficiency, inadequate calcium intake, sedentary lifestyle, chronic dieting, underlying chronic diseases, and the use of certain medications used to treat those diseases. After bariatric surgery, the risk for bone-related problems is even greater, owing to severely restricted intake, malabsorption, poor compliance with prescribed supplements, and dramatic weight loss. Patients presenting for bariatric surgery should be evaluated for MBD and receive appropriate presurgical interventions. Furthermore, every patient who has undergone bariatric surgery should receive meticulous lifetime monitoring, as the risk for developing MBD remains ever present.